Loss of TIMP3 expression induces inflammation, matrix degradation, and vascular ingrowth in nucleus pulposus: A new mechanism of intervertebral disc degeneration. Issue 4 (27th February 2020) - Li, Yan; Zhang, Ting; Tian, Wenjia; Hu, Hejia; Xin, Zengfeng; Ma, Xiaojing; Ye, Chenyi; Hang, Kai; Han, Xiuguo; Zhao, Jie; Li, Weixu
Abstract: Low back pain (LBP) is one of the most common complains in orthopedic outpatient department and intervertebral disc degeneration (IDD) is one of the most important reasons of LBP. The mechanisms of IDD contain a complex biochemical cascade which includes inflammation, vascular ingrowth, and results in degradation of matrix. In our study, we used both in vitro and in vivo models to investigate the relation between tissue inhibitor of metalloproteinase‐3 (TIMP3) expression and IDD. Loss of TIMP3 expression was found in degenerative intervertebral disc (IVD), this change of expression was closely related with the dephosphorylation of smad2/3. Overexpression of TIMP3 significantly inhibited the release of TNF‐α and matrix degradation induced by Lipopolysaccharide. Vascular ingrowth was also suppressed by TIMP3 in the in vitro and in vivo models. Further, animal experiments confirmed that the degeneration of IVD was reduced after overexpression of TIMP3 in nucleus pulposus. Taken together, our results indicated TIMP‐3 might play an important role in the pathogenesis of IDD and therefore be a potential therapeutic target in the future.